Working Capital Management of Small and Medium-Sized Enterprises (SMEs) in Accra, Ghana: The Perspective of Owner Managers’ Behavioral Biases - JEFF, LAMPTEY (UNIMAS, 2023)
This thesis aims to investigate the working capital management of Small and Medium-Sized Enterprises (SMEs) in Accra, Ghana from the perspective of owner managers’ behavioral biases. Knowledge about behavioral biases in working capital management has lagged despite the fact that most Small and Medium Enterprises (SMEs) managers who employed a subjective approach to working capital management may expose themselves to overconfidence, Loss aversion, anchoring, and adjustment biases. To address this concern, this thesis employed qualitative designs and obtained textual data through telephone interviews with thirty-five (35) SME owner-managers to obtain their perspective on these biases by exploring the basic assumptions of overconfidence theories (Better- than average effect; the illusion of control and excessive optimism and over the precision of knowledge), Loss aversion theory and anchoring and adjustment theory. Based on the thematic data analysis, this study finds support that SMEs owner-managers exhibit overconfidence, loss aversion, anchoring, and adjustment, influencing working capital management. Specifically, the results suggest that overconfident SME owner-managers believe that they possess superior financial ability, perfect industry knowledge and are optimistic about business success and wish to overinvest in working capital inventory if they have enough internal funds. Furthermore, the finding suggested that loss-averse SME owner-managers exhibited the fear of loss and costs disposition effects to the extent that highly loss-averse SMEs owner managers tend to underinvest in working capital inventory while low loss-averse SMEs managers tend to overinvest in working capital inventory. In terms of anchoring and adjustment bias, the results show that managers rely heavily on mental shortcuts or heuristics: self-generated and provided anchors in working capital management. More specifically, SMEowner-managers rely on customer trust, initial offers (price list,quotation), and market trends and demand (past and current sales). The premium managers attached to these anchors led them to either overinvest or underinvest in working capital. Specifically, low anchor (low initial offers and high growth market) tends to induce managers to increase working capital investment inventories while high anchor (high initial offer and declined market growth) discouraged SMEs managers to curtail working capital investment. Meanwhile, managers tend to grant more accounts receivable to highly trusted customers because of longstanding business relationships, taken as low default risk, than customers with a short-term business relationship. The study findings contribute by adding to the limited empirical evidence that exists on the influence of SMEs owner-manager overconfidence and inventory management, cash management, financing; SMEs owner managers’ loss aversion and inventory management and anchoring and adjustment bias of SMEs owner-managers, and inventory management, accounts receivable. By implication, the findings of this study support the theories of overconfidence, loss aversion theory, anchoring, and adjustment and add to broaden the scope of working management practices in SMEs. Finally, the study concludes that SMEs managers’ behavioral biases matter in working capital management.